Nasal packing: When a routine practice becomes a life‐threatening emergency. Issue 12 (16th August 2020) - Novoa, Eva; Junge, Helge
Abstract: Aspiration of unsecured nasal packs of any sort must be suspected in patients presenting with acute airway situations and a recent history of nose procedures. An immediate removal is mandatory to avoid long‐term complications and even death. Abstract : Aspiration of unsecured nasal packs of any sort must be suspected in patients presenting with acute airway situations and a recent history of nose procedures. An immediate removal is mandatory to avoid long‐term complications and even death.